The Impact of Digital Marketing, Price and Product Quality on Coffee Shopping Interest in The Coffee Shop - Barsilewin, Enjel Merry; Carla Rettobjaan, Vitalia Fina; Aristayudha, A A Ngurah Bagus (West Science Interdisciplinary Studies, 2024)
Bali is an exotic island in Indonesia, famous for its stunning natural beauty, rich in culture, the island is known as the “Dewata Island”. Besides its natural beauty Bali is also known as one of the best specialized coffee producers in the world. Bali Coffee has also become one of the leading agro industries in the Bali region. Bali coffee is a very promising commodity because its addictive nature makes it difficult for its fans to abandon this bitterly aspiring drink. The study aims to explore respondents' views on factors such as digital marketing, price and quality of products against interest in buying Coffee at Coffee Shop in Karangasem district. The research method used is quantitatively descriptive samples in this study are 100 people. On the results of the tests that have been carried out against the digital marketing variable (X1) against the buying interest variables (Y) where the influence that occurs is positive, on the result of the testing that has been done against the price variable, (X2) against the buy interest variable(Y), where the impact that occures is positive. On the test results that have taken place against the quality variable of the product (X3) against the purchase interest variabel (Y), digital marketing, price and quality of the products individually or jointly have a positive influence on the coffee shopping interest in the coffee shop in Karasemang district.